IN THE SIXTEENTH CENTURY THROUGH THE TEM UR AND SHEIBANIDS SOCIAL AND POLITICAL PROCESSES INSTEAD OF THE IMAGINATION - Kandakharov Anvarjon Khasanovich (International Journal of Innovations in Engineering Research and Technology, 2021)
This article reveals the socio-political life of the XVI century, in particular, the disputes between Zahiriddin Muhammad Babur and the Shaybanis, the activities of mystics who took an active part in political relations on the basis of historical sources. in particular, the participation of Sheikh Khudoydod Vali, a representative of the Yassaviya sect, in socio-political processes is revealed on the basis of sources. The article also provides information about the rise to power of the princes of the Shaybani dynasty and the life and work of the representatives of the mystical sect, who supported the rulers in the policy of centralization of the country, both politically and spiritually.